DIGITALIZATION AND MONETARY POLICY EFFECTIVENESS IN SHAPING REGIONAL ECONOMIC GROWTH - Mirzaraximov Avazbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This study provides an empirical analysis of the effects of digital technologies and monetary policy instruments on economic growth across Uzbekistan’s regions. Based on panel data covering the period from 2015 to 2025, the analysis demonstrates that the development of digital payment systems significantly enhances the efficiency of credit resource allocation to the real sector and accelerates monetary policy transmission mechanisms. The research findings confirm that digital technologies stimulate regional economic growth by reducing the time lags inherent in traditional monetary policy. The conclusions drawn highlight that enhancing digital financial inclusion is a strategic priority for mitigating regional economic disparities.